Thermal Performance of Flat Plate Solar Collectors for Humid and Unpredicted Weather using Air Properties and Energy Method (International Journal of Technology and Management Research, 2021)
Devising technologies to make use of renewable energy such as solar energy is very innovative and progressive sincetapping energy from a free source is cost effective in the long-term and totally ecologically friendly. The main aim ofsolar drying of crops is to preserve them by removing the excess moisture that will cause their deterioration in orderto improve their shelf life. Solar drying though found to be a mature, cost-effective and an efficient method ofdrying especially crops, it has not been widely deployed for crop drying both at the commercial and industrial levelin Ghana. The purpose of this research is to produce a solar heat collector for space heating using cheap andavailable materials and also to demonstrate the importance of incorporating obstacle/fins on plates to improve theefficiency of solar collectors. This study investigates the effect of increased air contact area of various configurationon the efficiency of solar air heaters. Nine different absorber plates (with and without fins) were considered by thisresearch in an experimental study to select the best design that will be suitable for absorbing or providing a highfraction of heat for conditioning humid atmospheric air (lowest relative humidity of the collector air). The bestdesigns of this study had an efficiency between 58% to 72% and maximum absorber temperatures above 80oC,collector air temperature above 70oC and collector air relative humidity below 20% while the worst design had anefficiency between 35% and 50%, collector air temperature bellow 45oC and the lowest collector air relativehumidity of 26%. The findings of this research have revealed that increasing the contact area of the air current orcirculation and the shapes of the fins attached to flat absorber plates increase their air contact areas and affect thethermal efficiency of the solar collectors. Also, it has revealed that the arrangement of fins contributes positively tothe efficiency of solar collectors.Citation: Felix Uba, Eric Osei Essandoh, Gilbert Ayine Okolo, Charles Nunya Dzikunu. Thermal Performance of Flat PlateSolar Collectors for Humid and Unpredicted Weather using Air Properties and Energy Method, 2020; 5(4): 30-49.Received: September 17, 2020Accepted: December 31, 2020
Keywords: Thermal performance; mat black; plates; collector; air properties; heat transfer coefficient